Testing protocol to obtain failure properties of asphalt binders at low temperature using creep compliance and stress-controlled strength test. (8th May 2017) - Marasteanu, Mihai; Ghosh, Debaroti; Cannone Falchetto, Augusto; Turos, Mugurel
Abstract : Good fracture properties are an essential requirement for asphalt materials used in the construction of pavements in cold regions. For asphalt binder, two instruments were developed during SHRP research effort to investigate the low-temperature behaviour of these materials: bending beam rheometer (BBR) and direct tension tester (DTT). These two devices are used to obtain the performance grade (PG) of asphalt binders in the US. The DTT is expensive and the results are less repeatable due to a complex sample preparation and difficult-to-achieve strain-controlled loading. For these reasons, many agencies do not use DTT when selecting asphalt binders, and rely entirely on the creep properties obtained with the BBR testing method. In this paper, a modified BBR is used to perform three-point bending strength tests on asphalt binder beams at low temperature, with the final goal of developing a specification for binder selection, similar to the current PG specification. BBR strength and DTT tests are first performed on a common set of binders, and the results are compared using size effect theory. Then, additional tests are performed and a simple and practical strength test procedure based on BBR creep data and on BBR strength data obtained under constant loading rate is proposed.